#### Answer

$x = -1$

#### Work Step by Step

$2(x-4-2x+3) = 2x+2$
$2x - 8 - 4x + 6 = 2x + 2$
$2x - 4x -2x = 2 + 8 - 6$
$-4x = 4$
$x = -1$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$x = -1$

$2(x-4-2x+3) = 2x+2$
$2x - 8 - 4x + 6 = 2x + 2$
$2x - 4x -2x = 2 + 8 - 6$
$-4x = 4$
$x = -1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.